Ethyl‐Zinc(II)‐Cation Equivalents: Synthesis and Hydroamination Catalysis. Issue 39 (11th August 2015) - Petersen, T. O.; Tausch, E.; Schaefer, J.; Scherer, H.; Roesky, P. W.; Krossing, I.
Abstract Ion‐like ethylzinc(II) compounds with weakly coordinating aluminates [Al(ORF)4]− and [(RFO)3Al‐F‐Al(ORF)3]− (RF=C(CF3)3) were synthesized in a one‐pot reaction and fully characterized by single‐crystal X‐ray diffraction, NMR and vibrational spectroscopy, and by quantum chemical calculations. The catalytic activity of ion‐like Et‐Zn[Al(ORF)4] in intermolecular hydroamination and in the unusual double hydroamination of anilines and alkynes was investigated. Favorable performance was also found in comparison to the Et2Zn/ [PhNMe2H]+[B(C6F5)4]− system generated in situ at lower catalyst loadings of 2.5 mol %.